Engineering of Hierarchical and Three‐Dimensional Architectures Constructed by Titanium Nitride Nanowire Assemblies for Efficient Electrocatalysis. Issue 8 (17th April 2019) - Liu, Fangfang; Yang, Xu; Dang, Dai; Tian, Xinlong
Abstract: Electrocatalysts that exhibit both, high performance and durability are essential for the promotion and commercialization of energy conversion devices. Transition metal nitrides (TMNs) hold great potential in many electrochemical catalytic processes, whereas the rational syntheses of highly open and three‐dimensional titanium nitride‐based nanostructures through a facile and efficient strategy is still a challenge. Herein, a scalable and effective method is proposed for the rational synthesis of mono‐ or bi‐metallic titanium nitride with three‐dimensional urchin‐like porous structures, which exhibit high electrochemical stability and structure durability. When being used as the support, the resultant electrocatalyst possesses much higher activity and durability in oxygen reduction reaction as well as methanol oxidation reaction. This work provides a general approach for the rational design of TMN‐based electrocatalysts or devices for application in energy conversion and storage technologies. Abstract : Titanomachy : a scalable and effective method is proposed for the rational synthesis of mono‐ or bi‐metallic titanium nitride with three‐dimensional urchin‐like porous structures as supporting material for the deposition of electrocatalysts. The three‐dimensional binary titanium nitride supported platinum catalysts exhibit high activity for both oxygen reduction reaction and methanol oxidation reaction.